Clinical Features of Asymptomatic SARS-CoV-2 Infection in Hemodialysis Patients - Maria Soledad Pizarro-Sánchez; Alejandro Avello; Sebastian Mas-Fontao; Teresa Stock da Cunha; Elena Goma-Garcés; Mónica Pereira; Alberto Ortíz; Emilio González-Parra (Karger Publishers, 2021)
Background: CKD is a risk factor for severe COVID-19. However, the clinical spectrum of COVID-19 in hemodialysis patients is still poorly characterized. Objective: To analyze the clinical spectrum of COVID-19 on hemodialysis patients. Method: A retrospective observational study was conducted on 66 hemodialysis patients. Nasopharyngeal swab PCR and serology for SARS-CoV-2, blood analysis, chest radiography, treatment, and outcomes were assessed. Results: COVID-19 was diagnosed in 50 patients: 38 (76%) were PCR-positive and 12 (24%) were PCR-negative but developed anti-SARS-CoV-2 antibodies. By contrast, 17% of PCR-positive patients failed to develop detectable antibodies against SARS-CoV-2. Among PCR-positive patients, 5/38 (13%) were asymptomatic, while among PCR-negative patients 7/12 (58%) were asymptomatic (p = 0.005) for a total of 12/50 (24%) asymptomatic patients. No other differences were found between PCR-positive and PCR-negative patients. No differences in potential predisposing factors were found between asymptomatic and symptomatic patients except for a lower use of ACE inhibitors among asymptomatic patients. Asymptomatic patients had laboratory evidence of milder disease such as higher lymphocyte counts and oxygen saturation and lower troponin I and interleukin-6 levels than symptomatic patients. Overall mortality was 7/50 (14%) and occurred only in symptomatic PCR-positive patients in whom mortality was 7/33 (21%). Conclusions: Asymptomatic SARS-CoV-2 infection is common in hemodialysis patients, especially among patients with initial negative PCR that later seroconvert. Thus COVID-19 mortality in hemodialysis patients may be lower than previously estimated based on PCR tests alone.